Impact of Consciousness Energy Healing Treatment on the Physicochemical and Thermal Properties of Silver Oxide - Dahryn Trivedi; Mahendra Kumar Trivedi; Alice Branton; Gopal Nayak; Snehasis Jana (Journal of Advanced Pharmaceutical Science And Technology, 2018)
Silver oxide (Ag2O) has the antimicrobial properties, which is insoluble in most of the solvents and sensitive to light. Therefore, this study was performed to evaluate the impact of the Trivedi Effect®-Consciousness Energy Healing Treatment on the physicochemical and thermal properties of Ag2O powder using modern analytical techniques. The Ag2O sample was divided into two parts, one part of the sample was considered as the control sample, whereas the other part of the sample received the Biofield Treatment remotely by a renowned Biofield Energy Healer, Dahryn Trivedi and termed as a treated sample. The particle size values were significantly decreased by 26.70% (d10), 20.67% (d50), 18.7% (d90), and 20.57% D(43), hence, the specific surface area was significantly increased by 32.33% in the treated Ag2O sample than control sample. PXRD peak intensities and crystallite sizes were significantly altered from -94.93% to 6.18% and -54.19% to 54.89%, respectively, however, the average crystallite size was significantly decreased by 14.66% in the treated sample compared with the control sample. The latent heat of fusion of the treated Ag2O was significantly decreased by 61.12% compared with the control sample.The total weight loss was significantly increased by 49.34%, hence, the residue amount was 4.05% less in the treated sample than the control sample.These results suggested that the Trivedi Effect® might introduce a new polymorphic form of Ag2O which would offer better solubility, absorption, and bioavailability of the pharmaceutical formulations and also be advantageous for the pharmaceutical industry when using it as a raw material.
Keywords: Silver Oxide